From the seat of a traditional Kingdom to a Garden city: the socio-spatial politics of managing green areas in Kumasi, Ghana. Issue 4 (2nd October 2019) - Amoako, Clifford; Adom-Asamoah, Gifty
Abstract: Established in 1817, Kumasi, Ghana's second largest city was accorded the accolade 'Garden city of West Africa' in the 1940s due to its beautiful green areas. Over its 200 years of existence, the city's development and morphology has been greatly shaped by its strong cultural, traditional and socio-political antecedents, rooted in its establishment as an important fortress of the Ashanti Kingdom. Today, Kumasi has lost its 'Garden city' accolade owing to poor management of these 'green areas'. This paper argues that the challenges of managing open spaces in Kumasi can be explained by the city's strong historical foundations and socio-political conflicts between indigenous/customary land ownership and state urban planning regime. Situated within the city's historical and socio-political contexts, the study draws on multiple qualitative methods including: document review, institutional consultations, key informant interviews, and field observations, to gather evidences. The paper reveals, that central to the problem of managing open spaces in Kumasi are the city's strong customary land ownership structures and socio-political history of conflicts between its traditional set-up and state officialdom . These conflicts are continuously being shaped by a complex state institutional framework, customary and communal land ownership structure.